Prevalence, clinical characteristics and treatment outcome of factor X deficiency in a consecutive cohort of primary light-chain amyloidosis. (September 2022) - Gao, Ya-juan; Shen, Kai-ni; Chang, Long; Feng, Jun; Mao, Yue-ying; Zhang, Lu; Cao, Xin-xin; Zhou, Dao-bin; Li, Jian
Abstract: Factor X (FX) deficiency is prevalent in light-chain (AL) amyloidosis but its clinical significance was not investigated deeply. We conducted a retrospective analysis of a consecutive cohort with 207 primary AL amyloidosis patients. FX deficiency was present in 129 patients (62.3%). Those with FX deficiency had higher dFLC (299.6 mg/L vs. 102.3 mg/L, P  < 0.001), higher cardiac troponin I (0.05 μg/L vs. 0.02 μg/L, P  < 0.001) and N-terminal pro-brain natriuretic peptide (3115 ng/L vs. 392 ng/L, P  < 0.001), and more patients with bone marrow plasma cells > 10% (18.0% vs. 4.3%, P  = 0.008). The prevalence of FX deficiency increased with the Mayo 2004 stage. FX-deficient patients exhibited inferior overall survival ( P  < 0.001) and progression-free survival ( P  < 0.001) than others. Fifty-five patients with FX deficiency received retesting of FX activity after anti-plasma cell therapy. The median variation in FX activity was + 6.8% (range, −24.5% ~ +73.4%). Better improvement of FX activity was observed in patients with complete hematologic response (+18.2% vs. +4.0%, P  = 0.036) and at least one organ response (+14.4% vs. +3.4%, P  = 0.024). FX deficiency is associated with a heavier disease burden and poorer survival in primary AL amyloidosis. Improvement of FX activity tends to appear in patients with better hematologic and organ responses after chemotherapy. Highlights: Factor X deficiency is common in patients with light-chain amyloidosis. Presence of factor X deficiency at diagnosis is not related to treatment response. Factor X deficiency is related to a heavier disease burden and poorer survival. Improvement of FX activity appears in patients with better treatment responses.